The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1981
DOI: 10.1111/j.1600-0714.1981.tb01246.x
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of gingival sulcular epithelium in the development of scorbutic gingivitis

Abstract: Young adult nonhuman primates were initially fed an ascorbic-acid free diet and, subsequently, a diet with a suboptimal level of the vitamin. Following approximately 12 weeks of this dietary regime, five of seven experimental animals developed scorbutic gingivitis. 2 to 3 weeks prior to this stage, the permeability of the gingival sulcular epithelium to ^H-inulin, but not to ^^C-butyric acid or ''C-urea, had increased significantly (+86%, P < 0.01) in the experimental group as compared to ad libitum or pair-fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

1981
1981
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…[1][2][3][4][5][6][7] One of the important roles of vitamin C in metabolic function is collagen synthesis, particularly in the course of wound healing. This is relevant for the maintenance of oral tissues such as the periodontal ligament, the formation of bone matrix and the integrity of blood vessel walls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] One of the important roles of vitamin C in metabolic function is collagen synthesis, particularly in the course of wound healing. This is relevant for the maintenance of oral tissues such as the periodontal ligament, the formation of bone matrix and the integrity of blood vessel walls.…”
Section: Discussionmentioning
confidence: 99%
“…Systemic factors such as a balanced nutrition or nutritional supplementation have not been thoroughly evaluated in periodontal research, although reports of the possible effects of nutrient deficiency and supplementation have appeared early in the periodontal literature. [1][2][3][4] The relationship between vitamin C and periodontal disease has been of interest ever since it was observed that people with vitamin C deficiencies have loose teeth and red swollen gingiva. Former studies have dealt with the effect of vitamin C supplementation in the treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Following the ascorbic acid injections (week 12), body weight of the experimental animals increased steadily and leveled off at week 21. Likewise, food intake also improved such that between week 21 and the end of the study the experimental animals consumed only 14 % less than normal for ad libitum animals (Worthington, Alvares & Ahmed 1979, Alvares & Siegel 1981.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that acute ascorbate deficiency increases the permeability of the gingival sulcular epithelium and that this change occurs prior to the development of scorbutic gingivitis (Alvares & Siegel 1981). This finding led us to suggest that acute ascorbate deficiency might permit greater penetration of antigenic materials from the gingival crevice into the underlying connective tissue and thereby contribute to the pathogenesis of scorbutic gingivitis.…”
Section: Introductionmentioning
confidence: 97%
“…심각한 비타민 C 결핍은 괴혈병을 유발하 며, 이는 궤양성 치은염과 치아 박리 및 빠른 치주낭 형성을 특징 으로 한다 12,14) . 비타민 C 결핍은 프롤린(proline)의 수산화반응 (hydroxylation)에 영향을 주며 구강점막 내 독소의 투과성이 증 가하여 콜라겐 합성에 어려움이 있으며 15) , 치아의 경조직과 연조 직 모두가 퇴화되어 치주조직에 부정적인 영향력을 주는 것으로 보고하였다 12,15,16) . Table 1).…”
unclassified